Hungary : 2007 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
Hungary's 2007 Article IV Consultation reports that with fiscal consolidation on track for 2007 and 2008, short-term risks have receded, especially owing to the favorable international financial environment. Ensuring that the current economic slowdown does not translate into a prolonged period of low growth is important both for raising standards of living and for containing vulnerabilities. Putting the debt on a sustainable downward trend will also require a substantial decrease in the size of government expenditure in relation to GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet